2009
DOI: 10.1136/thx.2008.106237
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences and predictors of objective cough frequency in chronic cough

Abstract: Background: Women are consistently over-represented in specialist cough clinics and known to have a more sensitive cough reflex than men. Whether female sex and other patient characteristics are associated with higher cough rates is not known. A study was conducted to determine the predictors of objective cough frequency in patients presenting to a tertiary referral clinic with chronic cough. Methods: 100 subjects (65 women) of mean (SD) age 55.8 (11.0) years and median cough duration 4 years (IQR 2.0-10.0) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
71
3
16

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 43 publications
13
71
3
16
Order By: Relevance
“…This raises the possibility that similar mechanisms drive both acute and chronic coughing and one study has indeed suggested that one-third of chronic cough patients report their cough being initiated by an URTI [16]. Unlike in chronic cough [32], we did not observe any significant influence of age or sex on objective cough frequency in this study population, but the sample size may have been insufficient to detect these effects. This is, however, consistent with the finding that males and females with an acute cough have similar cough-specific quality-of-life scores, in contrast with chronic cough, where females have worse scores than males [15].…”
Section: Discussioncontrasting
confidence: 50%
“…This raises the possibility that similar mechanisms drive both acute and chronic coughing and one study has indeed suggested that one-third of chronic cough patients report their cough being initiated by an URTI [16]. Unlike in chronic cough [32], we did not observe any significant influence of age or sex on objective cough frequency in this study population, but the sample size may have been insufficient to detect these effects. This is, however, consistent with the finding that males and females with an acute cough have similar cough-specific quality-of-life scores, in contrast with chronic cough, where females have worse scores than males [15].…”
Section: Discussioncontrasting
confidence: 50%
“…Females have a heightened sensitivity of the cough reflex as revealed by inhalational challenge with citric acid [17,18], tartaric acid [19], and capsaicin [20]. This increased sensitivity of the cough reflex is also demonstrable in patients attending the cough clinic [21] where objectively recorded cough in females is twice that of males [18]. Together these observations would suggest that females have an increased sensitivity of the cough reflex in comparison with males.…”
Section: Discussionsupporting
confidence: 49%
“…Twice as many females as males develop a cough on angiotensin-converting-enzyme inhibitor therapy [16]. Females have a heightened sensitivity of the cough reflex as revealed by inhalational challenge with citric acid [17,18], tartaric acid [19], and capsaicin [20]. This increased sensitivity of the cough reflex is also demonstrable in patients attending the cough clinic [21] where objectively recorded cough in females is twice that of males [18].…”
Section: Discussionmentioning
confidence: 95%
“…We have developed an ambulatory system for making sounds recordings over 24 hours in ambulatory patients, which allows the objective quantification of coughing (Vitalojak; Vitalograph Ltd., Buckingham, UK). This system has provided novel insights into the predictors of cough in patients presenting with isolated chronic cough (14,15), asthma (16), and cystic fibrosis (17).…”
mentioning
confidence: 99%